2021
DOI: 10.1016/j.jds.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and biocompatibility of the mixture of mineral trioxide aggregate and nitric oxide-releasing compound

Abstract: Background/purpose Antimicrobial activity and biocompatibility of root canal sealer are related to the success of endodontic treatments. This study investigated the efficacy of mixture of mineral trioxide aggregate (MTA) and a NO-releasing compound for the antimicrobial activity, biocompatibility, and physical properties. Materials and methods MTA was mixed with diethylenetriamine-NO (MTA-NO), and the extracts from MTA and the MTA-NO mixture before and after setting was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…In a more recent study, it was found that MTA HP was not effective over P. gingivalis [ 18 ], and these outcomes agree with the reported results in the present study, in which MTA HP was not effective over none of the tested anaerobic bacteria except of P. micra . Besides, there is only one study in the literature that evaluated the effect of MTA over P. endodontalis in which the effectivity of MTA was improved with the addition of nitric oxide [ 19 ]. According to the same study, the antimicrobial action of the CSC is affected by its setting [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study, it was found that MTA HP was not effective over P. gingivalis [ 18 ], and these outcomes agree with the reported results in the present study, in which MTA HP was not effective over none of the tested anaerobic bacteria except of P. micra . Besides, there is only one study in the literature that evaluated the effect of MTA over P. endodontalis in which the effectivity of MTA was improved with the addition of nitric oxide [ 19 ]. According to the same study, the antimicrobial action of the CSC is affected by its setting [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there is only one study in the literature that evaluated the effect of MTA over P. endodontalis in which the effectivity of MTA was improved with the addition of nitric oxide [ 19 ]. According to the same study, the antimicrobial action of the CSC is affected by its setting [ 19 ]. In the present study, only 5MO was effective over P. endodontalis.…”
Section: Discussionmentioning
confidence: 99%
“…Perforations in the roots are one of the reasons for failure in endodontics, and if they are not detected and corrected promptly, they can result in the loss of the affected teeth. MTA has several desirable properties for endodontic repair, including strong sealing ability, biocompatibility, antibacterial properties, and hydrophilic behavior ( Shin et al, 2021 ).…”
Section: Mta Modifications With Improved Characteristics and Applicat...mentioning
confidence: 99%
“…Various studies have linked five– seven bacterial species to root canal infection, with Porphyromonas gingivalis , Porphyromonas endodontalis , and Enterococcus faecalis being the most often isolated bacterial species from pulpitis. Apical periodontitis is linked to Enterococcus faecalis in RC-treated teeth, whereas Porphyromonas endodontalis and Porphyromonas gingivalis are related to the infection of the root canal (RC) ( Shin et al, 2021 ). Because the root canal system is anatomically complex, the complete elimination of pathogenic microorganisms in the root canal is challenging.…”
Section: Mta Modifications With Improved Characteristics and Applicat...mentioning
confidence: 99%
“…Many studies are available on the antibacterial properties of MTA. Several investigations have demonstrated limited antibacterial properties of MTA against some microorganisms [29][30][31][32] . A study on facultative and obligate anaerobes showed that [30] MTA had antibacterial effects on some facultative anaerobes, with little impact on strict obligate anaerobes.…”
Section: Introductionmentioning
confidence: 99%